Evaluation of critical rest interval determined from repeated sprint ability testing - La Monica, M. B.; Fukuda, D. H.; Beyer, K. S.; Hoffman, M. W.; Miramonti, A. A.; Fragala, M. S.; Stout, J. R.; Hoffman, J. R. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: To test if the critical power (CP) concept can be utilized to determine the critical rest interval (CRI) using repeated sprint ability (RSA) testing with varying work-to-rest ratios.